2018
DOI: 10.1111/ijcs.12417
|View full text |Cite
|
Sign up to set email alerts
|

Me, my family or the public good? Do inter‐role conflicts of consumer–citizens reduce their ethical consumption behaviour?

Abstract: This article examines role stress, especially inter-role conflicts (IRC), against the background of the consumer-citizen duality. It tests whether consumer-citizen conflicts impair the purchase of ethical food in terms of the ethical intention-behaviour gap. Furthermore, this study examines the potential of eustress arising from citizen-consumer conflicts to enhance actual ethical purchases.Additionally, determinants and moderating conditions of both IRC are tested. A combination of observations of actual purc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 74 publications
(121 reference statements)
0
20
0
Order By: Relevance
“…Modelers endeavor to reveal constructs that add new insights to the current research because they are convinced that social desirability and methodological limitations account for only a minor part of the gap (Carrington et al, 2010;Verbeke & Vermeir, 2006). Purchase barriers such as price (e.g., value for money) (Padel & Foster, 2005), availability (Tarkiainen & Sundqvist, 2009), quality (e.g., taste and appearance) (Loebnitz, Schuitema, & Grunert, 2015), situational factors (e.g., promotion and role conflicts) (Frank, 2018;Van Doorn & Verhoef, 2015), and information (e.g., lack of knowledge, lack of trust, certificate diversity) (Gruber, Schlegelmilch, & Houston, 2014;Padel & Foster, 2005) are often the subject of research interest. Bridging essential purchase barriers while accounting for methodological aspects seems to be the key to more organic purchase behaviors.…”
Section: Organic Ibg: Methodologists and Modelermentioning
confidence: 99%
“…Modelers endeavor to reveal constructs that add new insights to the current research because they are convinced that social desirability and methodological limitations account for only a minor part of the gap (Carrington et al, 2010;Verbeke & Vermeir, 2006). Purchase barriers such as price (e.g., value for money) (Padel & Foster, 2005), availability (Tarkiainen & Sundqvist, 2009), quality (e.g., taste and appearance) (Loebnitz, Schuitema, & Grunert, 2015), situational factors (e.g., promotion and role conflicts) (Frank, 2018;Van Doorn & Verhoef, 2015), and information (e.g., lack of knowledge, lack of trust, certificate diversity) (Gruber, Schlegelmilch, & Houston, 2014;Padel & Foster, 2005) are often the subject of research interest. Bridging essential purchase barriers while accounting for methodological aspects seems to be the key to more organic purchase behaviors.…”
Section: Organic Ibg: Methodologists and Modelermentioning
confidence: 99%
“…An explanation of the five categories was given to ensure a common understanding and perception. This procedure reduced biases concerning the topic of interest and socially desired purchases and assured virtually normal purchase behavior (Frank, ; Oh & Yoon, ).…”
Section: Methodsmentioning
confidence: 99%
“…The results of these studies are inconclusive because, when focusing on the phenomenon of the IBG, the applied method should reflect its special character (e.g., selecting participants with high buying intention; Aschemann‐Witzel & Niebuhr Aagaard, ; Frank, ). Additionally, research has revealed that buying ethical groceries appears due to several different self‐oriented, altruistic, and/or biospheric reasons (van Doorn & Verhoef, ; Vega‐Zamora et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations